The Influence of Transformational Leadership, Organizational Culture, Work Environment, and Training on Radio Broadcaster Performance of Tirilolok Swara Verbum, Kupang with Listener Activity as an Intervening Variable (Case Study at Tirilolok Swara Verbum Radio Kupang) - Dismas Longginus Mauk; John E.H.J. FoEh (Dinasti Publisher, 2025)
This study aims to analyse the influence of transformational leadership, organizational culture, work environment, and training on broadcaster performance, with listener activity as an intervening variable. The method used is quantitative and literature- based, with data collected through observation and questionnaires at Tirilolok Swara Verbum Radio. The results indicate that all four independent variables significantly affect broadcaster performance, both directly and through listener activity. Listener activity is proven to be an important bridge that strengthens the relationship between organizational factors and improved broadcaster performance. These findings highlight the crucial role of listeners in creating dynamic, innovative, and professional broadcasting.